Peran manajemen risiko dalam meningkatkan kinerja perusahaan: studi manajemen sumber daya manusia - Muhammad Asir; Yuniawati, Rizqy Aiddha; Mere, Klemens; Sukardi, Karina; Anwar, Muh. Abduh. (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2023)
The purpose of this paper is to analyze the Role of Risk Management in Improving Company Performance by analyzing research literature in the field of human resource management. The method used in this research is literature research by reviewing some of the results of previous studies. This scientific article was written using qualitative methods and research literature with the help of the latest references obtained from Google Schoolers and Mendeley citation searches. Based on the studies conducted, it means that risk management has a role in company performance. Therefore, risk management has a positive role in company performance. Risk management is one of the references used to manage existing resources within the company, so that the company can obtain good value and generate profits as expected by the company.